PEMBUKTIAN TINDAK PIDANA PERJUDIAN DENGAN MODUS MESIN PERMAINAN DI KEPOLISIAN RESOR KOTA PEKANBARU - Destrian Hasugian; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the city of Pekanbaru common criminal offenses gambling with the game engine mode, particularly at nightclubs , malls and game center. The culprit was not only done by adults only, but children also play this gambling. It is of course very worrying when viewed in terms of morale and the future of the perpetrator. The purpose of this thesis, namely : First What is proving the crime of gambling with the mode of the game engine at the City Police Pekanbaru, Secondly, What are the obstacles in proving the crime of gambling with the mode of the game engine at the City Police Pekanbaru, Third, How are the overcome the constraints of proving the crime of gambling by mode in the game engine Pekanbaru City Police. This research is a kind of sociological research is also descriptive. Source of data used were obtained through three (3 ) legal materials is the primary legal materials, secondary and tertiary. The data collection techniques were done by two methods is interviews and review of the literature. From the results of research and discussion, there are three main things that can be inferred. First, Verification carried out by investigators go directly to the location of gambling by going undercover and make arrests in accordance with Standard Operating Procedure. Secondly, the obstacle in proving the crime of gambling with the mode of the game engine, to fool the police with a reason to have a business license, the disagreements between the engineers with the investigator, the lack of human resources, lack of infrastructure, lack of awareness and legal awareness, the difficulty of finding evidence. Third, efforts to overcome obstacles, their understanding of the law is not the same between engineers with investigators, conduct learning activities specifically for the police, complete infrastructure, conduct legal counseling, conduct patrols and routine surveillance, formed a special team to spy spying place often used as a means gambling game machines. Suggestions, First, police officers with firmly and quickly cope with the crime of gambling with the game engine mode in Pekanbaru City area and in the process in order to promote the interests of the investigator. Second, the development of information technology very quickly will also affect the growth of types and patterns of crime. Third, the need for improved public awareness of the law. the need for the role of the public to assist the police in combating gambling with the mode of the game machine and so also against the police to provide legal counseling to the community, especially to discuss and talk about the impacts of gambling with the game engine mode for the creation of security and morality in society. Keywords : Evidence - Crime of Gambling - Game Engine